Sustainable development strategy for cultural heritage conservation of Hengshan cliff carving in Hunan province, people’s republic of China - Hao, Wu; Khiatthong, Thongchue (Edelweiss Applied Science and Technology, 2024)
Stone carving is unique to the People’s Republic of China (PRC) and has a long history of use. Therefore, it is the focus of research on sustainable development strategy for Hengshan Cliff Conservation carving cultural heritage calligraphy in Hunan Province, People’s Republic of China. The objectives of this research are (1) to study and analyze the conservation status of the cultural heritage of the Hengshan cliff carving. (2) Analyze and synthesize sustainable calligraphy cultural heritage development strategies for the conservation of the Hengshan cliff carvings. (3) Evaluate a strategy for the development of sustainable calligraphy cultural heritage for the conservation of Hengshan cliff carvings. This study uses a combination of qualitative and quantitative research methods. Qualitative research uses literature reviews related to cultural heritage conservation and sustainable development and interviews with stakeholders. Quantitative research uses survey methods distributed to experts in the field of Hengshan cliff carving calligraphy and to site visitors. The results showed that: (1) the preservation of Hengshan cliff carving calligraphy cultural heritage today has challenges and opportunities that have significant strengths and weaknesses. (2) The analysis and synthesis of sustainable development strategies on the key issues of environmental protection, preservation of cultural values, community participation, and policy support are important for the formulation of effective conservation strategies. (3) A sustainable development strategy is formulated and evaluated based on the indicators identified in the strategic area, including recommendations for improving conservation practices. However, from the questionnaires and 404 sets of samples collected, as well as interviews with experts and related parties, it can be summarized in an overview of various dimensions. The strength dimension was determined to be the average and standard deviation (4.480.43). The weak dimension has an average and standard deviation (4.480.44). The second-highest opportunity dimension was averaged and the standard deviation (4.400.44). The threat dimension was at the lowest level, with average and standard deviations (4.300.52). This indicates that respondents generally believe that the cultural heritage of Hengshan Cliff calligraphy is balanced in terms of strengths and weaknesses and that there are still opportunities for improvement, but the threats faced should not be ignored.